Peer Helping in an Intercollegiate Athletic Environment - Waalkes, Deanna M.; Yukelson, David P.; Hale, Bruce D.; Wheeler, Toni M. (My University, 1999)
Intercollegiate student-athletes face a variety of unique responsibilities and stressors. Balancing practice, training, traveling, and academics can be overwhelming. To assist student-athletes with these issues, the peer helper program called the Student Peer Athlete Network (SPAN) was developed. SPAN was designed to train specific student-athletes in peer helper skills so they, in turn, can assist other student-athletes who need support or assistance for certain personal, academic, or athletic concerns. Empowering student-athletes promotes a sense a self-responsibility and benefits the entire student-athlete population.
Keywords: peer programs